2018
DOI: 10.1139/cjm-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antimicrobial resistance to extended-spectrum cephalosporin, quinolones, and vancomycin in selected human enteric pathogens from Prince Edward Island, Canada

Abstract: The aim of this study was to determine the frequency of fecal carriage of vancomycin-resistant Enterococcus spp. and Escherichia coli with reduced susceptibilities to extended-spectrum cephalosporins (ESCs) and quinolones in humans on Prince Edward Island, Canada. Convenience fecal samples from individuals on Prince Edward Island were screened phenotypically using selective culture and genotypically using multiplex polymerase chain reactions to detect E. coli and Enterococcus spp. resistant to critically impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…In the present study, we detected four different groups of β-lactamases ( bla CMY-2 , bla TEM , bla SHV , and bla CTXM compared to previous studies in Nova Scotia, Canada(Forward et al 2004), Western Canada (Sheikh et al 2012), and USA (Doi et al 2010; Zhao et al 2012; Sjölund-Karlsson et al 2013)that reported only bla CMY-2 and bla TEM as the molecular basis for resistance to β-lactams in retail meat products. In addition, the β-lactamase genes detected in the present study have been reported either singly or in combination in chickens(Chalmers et al 2017), pigs(Kozak et al 2009; Jahanbakhsh et al 2016), cattle (Martin et al 2012; Cormier et al 2016; Awosile et al 2018b), dog (Zhang et al 2018), and as well as in humans in Canada (Denisuik et al 2013; Awosile et al 2018a). In all these studies, resistance to ESCs was predominantly mediated by bla CMY-2 , which corroborates the findings of the current study.…”
Section: Discussionsupporting
confidence: 55%
“…In the present study, we detected four different groups of β-lactamases ( bla CMY-2 , bla TEM , bla SHV , and bla CTXM compared to previous studies in Nova Scotia, Canada(Forward et al 2004), Western Canada (Sheikh et al 2012), and USA (Doi et al 2010; Zhao et al 2012; Sjölund-Karlsson et al 2013)that reported only bla CMY-2 and bla TEM as the molecular basis for resistance to β-lactams in retail meat products. In addition, the β-lactamase genes detected in the present study have been reported either singly or in combination in chickens(Chalmers et al 2017), pigs(Kozak et al 2009; Jahanbakhsh et al 2016), cattle (Martin et al 2012; Cormier et al 2016; Awosile et al 2018b), dog (Zhang et al 2018), and as well as in humans in Canada (Denisuik et al 2013; Awosile et al 2018a). In all these studies, resistance to ESCs was predominantly mediated by bla CMY-2 , which corroborates the findings of the current study.…”
Section: Discussionsupporting
confidence: 55%
“…In a Canadian study, ampicillin-resistant strains were identified while enrofloxacin-resistant strains demonstrated sensitivity; in a German study, on the other hand, the isolates were resistant to enrofloxacin ( Grobbel et al , 2007 ). In Spain, tetracycline resistance and reduced resistance to cephalosporins were identified in 80% of Proteus strains, and sensitivity to gentamicin was identified ( Awosile et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%